A Design Framework for Negative Poisson's Ratio Structure with Curved Beam‐Compliant Mechanism Unit Cells. Issue 7 (4th April 2022) - Lin, Sheng; Liu, Congyang; Hu, Qingyuan; Zhai, Yun; Wang, Xinning; Wang, Qi
Abstract : Negative Poisson's ratio (NPR) structures, also known as auxetics, are attracting growing interest due to their unique mechanical properties and a wide range of potential deployment. More attention has been paid to explore novel auxetic structures through bionics, lattice cells, or origami. However, the systemic design method of NPR structures has not yet matured. Herein, a design framework of NPR structures is proposed by integrating freedom, actuation, and constraint topologies (FACT) theory and isogeometric analysis. Based on the isogeometric method, the shape and mechanical properties of the curved beam can be changed by adjusting the control points of the curved beam. The configuration library is established by encapsulating curved beams to the straight beam. FACT theory is used to synthesize the cellular structure whose compliant elements are chosen from the curved beam configuration library. In this way, two NPR structures are designed. Simulation and experiments demonstrate the feasibility of the proposed design framework of NPR structure. The results of this study have a wide range of potential applications for designing future NPR structures. A new idea to design architected metamaterial systems exhibiting other properties is provided. Abstract : A common design framework for negative Poisson's ratio (NPR) structures with curved beam‐compliant mechanism unit cells is proposed. This helps designers choose the compliant curved beam with mechanical properties from the curved beam configuration library to build the structure. Then, a NPR structure with the expected properties can be used.